Role of IKKαα in skin squamous cell carcinomas. (January 2011) - Park, Eunmi; Liu, Bigang; Xia, Xiaojun; Zhu, Feng; Jami, Willette-Brown; Hu, Yinling
Squamous cell carcinoma (SCC) and basal cell carcinoma (BCC) are two major types of skin cancer derived from keratinocytes. SCC is a more aggressive type of cancer than BCC in humans. One significant difference between SCC and BCC is that SCC development is generally associated with cell dedifferentiation and morphological changes. When SCC is converted to spindle cell carcinoma, the latest stage of cancer, the tumor cells change to a fibroblastic cell morphology (epithelial-to-mesenchymal transition) and lose their differentiation markers. Recently, several laboratories have reported altered IκκB kinase αα (IKKαα) protein localization, downregulated IKKαα, and IKKαα gene deletions and mutations in human SCCs of the skin, lung, esophagus, and neck and head. In addition, IKKαα reduction promotes chemical carcinogen- and ultraviolet B-induced skin carcinogenesis, and IKKαα deletion in keratinocytes causes spontaneous skin SCCs, but not BCCs, in mice. Thus, IKKαα emerges as a bona fide skin tumor suppressor. In this article, we will discuss the role of IKKαα in skin SCC development.